Contribuições do modelo cognitivo comportamental para as práticas psicopedagógicas - Moss, Lucila Polity (2018)
The present work is a case study that aims to understand how the main techniques of the Behavioral Cognitive Model, proposed by Aaron Beck, can contribute to the psychopedagogical practice, in the light of Postmodern science. In the theoretical foundation are presented panoramas of the PostmodernScienceand the Cognitive Behavior Model. The latter assumes that events are thought-triggers and that these, in turn, will determine aperson's emotional, behavioraland physiological reactions. As a methodology for this study 25 individuals appointments were developed with an 11 year old child with cognitive, emotional and relational deficits, resulting in learning difficulties, aggressiveness, impulsivity, enuresis, inappropriate attitudes and sexual exacerbation. Among the activities developed are those of psychoeducation, affective monitoring and training of social skills, worked mainly through games and stories. It is also presented how these proposed techniques were adapted to the reality of the subject, considering their age group and their cognitive and emotional development. Networking was contemplated in parental and school orientation, aiming at the integration between the diverse social contexts of the individual. The study demonstrates that throughout the process, important development in different aspects of the subject has been verified and that the Cognitive Behavior Model has much to contribute to the psychopedagogical practice, since it enablesthe personto know and to modify its system of dysfunctional beliefs, especially those related to learning. At the end of the process, the pedagogical performance of the client showed considerable growth. In the same way, hebegan to realizemoments of greater anxiety and impulsivity, requestingforhelp. This model, therefore, proved to be enriching in addressing here-and-now dysfunctional situations, enabling immediate changes in behavior and favoring the development of more functional attitudes and beliefs in a short period of time